Assessment of Monkeypox (MPOX) Knowledge and Vaccination Intention among Health and Life Sciences Students in Algeria: A Cross-Sectional Study - Mohamed Lounis; Ahmed Hamimes; Ali Dahmani (MDPI AG, 2024)
Monkeypox (MPOX) is a viral zoonotic disease affecting endemically the Central and Western regions of Africa. The ongoing outbreak in non-endemic countries has made this disease a global concern. While no cases have been reported in Algeria, it is important to raise awareness about the disease to prepare for a potential outbreak, especially in light of the cases reported in neighboring Middle East and North African (MENA) countries. This study aimed to evaluate the knowledge and attitude of Algerian Health and Life Sciences students toward MPOX and its vaccine through an anonymous online survey. A total of 196 students participated in this study. Students of medicine (64.3%), females (85.7%), and those under 20 years of age (55.1%) were the most represented. The results revealed a low level of knowledge represented by a score of only 42.8% for correct answers with multiple gaps in epidemiology, etiology, and clinical manifestations of MPOX. Students of veterinary sciences showed the highest levels of knowledge (OR: 6.71; CI95%: 1.23-36.77), while those aged between 20 and 30 years old (OR: 0.11; CI95%: 0.02-0.79) and those vaccinated against seasonal flu (OR: 0.42; CI95%: 0.21-0.85) were associated with low levels of knowledge. Regarding MPOX vaccination, the study found a moderate level of acceptance (48.5%) among the surveyed students with Natural and Life Sciences students and those having a high vaccine conspiracy belief score (VCBS) showing the lowest level of acceptance. These findings highlight the need for educational programs and intensified public awareness campaigns to improve knowledge about MPOX and emphasize the importance of vaccination in preventing outbreaks and overcoming vaccine reluctance.